2018
DOI: 10.1371/journal.pone.0197980
|View full text |Cite
|
Sign up to set email alerts
|

Proximal fibular osteotomy to treat medial compartment knee osteoarthritis: Preoperational factors for short-term prognosis

Abstract: ObjectiveThe purpose of this study was to determine the association between preoperational factors and patients’ short-term outcome after proximal fibular osteotomy (PFO) and to provide a basis for detailed surgical indication and patient selection.MethodsThis was a retrospective study of patients undergoing PFO between January 2015 and December 2015. Preoperational clinical data including gender, age, duration of disease, visual analogue score (VAS) and American Knee Society (KSS) score were collected. The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 24 publications
0
48
2
2
Order By: Relevance
“…Liu et al [30] reported on 84 patients and 111 knees who had undergone PFO with a follow-up of 1 year. This is one of the largest series reported, in terms of numbers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al [30] reported on 84 patients and 111 knees who had undergone PFO with a follow-up of 1 year. This is one of the largest series reported, in terms of numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [26] advocates removing a 1-cm segment of fibula 7-8 cm from the head of the fibula by accessing it through the inter-muscular space between the extensor digitorum longus and peroneus longus/peroneus brevis, under local anesthesia. Others have used an approach between the peroneus and the soleus and removed a 2-cm segment 6-10 cm below the fibular head [20,30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous findings, our group established the “non‐union settlement theory,” which was firstly applied in knee osteoarthritis. We found the ratio of settlement of medial tibial plateau was decreased faster than that of the fibular part.…”
Section: Introductionmentioning
confidence: 99%
“…By using this method, researchers found that the neck shaft angle of the femur and femoral neck torsion angle of the Asian population were significantly decreased, whereas acetabular anteversion angle was remarkably increased with aging. Additionally, a previous study found that, with aging, medial tibial plateau was decreased and genu varum was accelerated, accompanied by increased proximal fibular curve angle. In the occurrence and progression of degenerative osteoarthritis, the tibial plateau settlement value was increased with the upgrading of Kellgren and Lawrence grades, which is a common method of classifying the severity of knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%